Censorship detected in TR (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Turkey. Data sourced from OONI.
Censorship Incident ID: TR-2026-0281. Severity: critical. Confidence: 73%